Bangladesh -- rolling up our sleeves: research on the front lines - International Food Policy Research Institute (International Food Policy Research Institute, 2002)
This brochure describes fully the work of The Food Management and Research Support Project, funded by the U.S. Agency for International Development (USAID) and implemented by the International Food Policy Research Institute. The project was designed to provide timely and relevant policy analysis and to help develop capacity to formulate sound food policies. From August 1997 through June 2001, IFPRI collaborated with theFood Planning and Monitoring Unit (FPMU) of the Bangladesh Ministry of Food as well as three subcontractors: the Bangladesh Institute of Development Studies (BIDS), the University of Minnesota, and the International Science and Technology Institute. The project consisted of three major activities: policy research on key issues in food management and food security and dissemination of research findings through workshops and seminars; provision of food policy advisory services; and training in food policy analysis for government officials. This fruitful collaboration between IFPRI, the Government of Bangladesh, and their partner institutions is an instructive example of how sharing information and skills can help developing countries move closer to their policy goals and improve the lives of their people.